2019
DOI: 10.1007/s12540-019-00310-6
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Spreading and Wettability of Abrasive Processed Aluminum Alloy Surfaces

Abstract: One of the main cause of a droplet metastable state is found to be surface roughness. This state is characterized by a large contact angle hysteresis and condition when the static contact angle is larger than the advancing dynamic contact angle. Besides the texture, other factors can influence the deviation from the equilibrium state, in particular, the fluid flow rate (the growth rate of a droplet) affecting the contact line speed. An experimental study was done to determine the effect of roughness and fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 41 publications
0
11
0
3
Order By: Relevance
“…Those researches focus on asperities and roughness phenomena, although the effect of cracks is suggested. Cracks on 3% coating might provoke an effect of pinning and the presence of the partial slip-condition along the rough surfaces on the liquid, being the change in wettability of this coating dependent on roughness and the geometric shape of cracks, as found in [54]. Moreover, it has also been suggested that special geometrical microstructures, together with trapped air in the closed structures, as can happen in found cracks, whose geometry has not been studied, may lead even to superhydrophobic properties on a hydrophilic surface [55], although just a decrease of hydrophilicity can take place, as shown in Fig.…”
Section: Morphological and Surface Characterizationmentioning
confidence: 93%
“…Those researches focus on asperities and roughness phenomena, although the effect of cracks is suggested. Cracks on 3% coating might provoke an effect of pinning and the presence of the partial slip-condition along the rough surfaces on the liquid, being the change in wettability of this coating dependent on roughness and the geometric shape of cracks, as found in [54]. Moreover, it has also been suggested that special geometrical microstructures, together with trapped air in the closed structures, as can happen in found cracks, whose geometry has not been studied, may lead even to superhydrophobic properties on a hydrophilic surface [55], although just a decrease of hydrophilicity can take place, as shown in Fig.…”
Section: Morphological and Surface Characterizationmentioning
confidence: 93%
“…can be increased not only by improving its design and applied technology but also by upgrading processing methods of engineering surfaces of this equipment. Enhancement of wetting properties can provide lubrication and help to reduce wear and friction [1], intensify heat removal in cooling systems [2], increase the efficiency of collecting water droplets in the chamber of droplet catchers [3], etc. This is possible by applying a coating to a previously prepared surface or modifying the surface to obtain unique functional properties (e.g., corrosion-resistant, anti-icing, superhydrophobic, and self-cleaning [4][5][6][7][8]) by different methods, such as plasma spraying [9], chemical vapor deposition [10], laser irradiation [11], etching [12], and different polishing methods [13].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…After polishing, the samples are used as the raw part for subsequent modifications or reference samples. Polished surfaces are taken as conditionally smooth [1,29]. Herewith, the changes in the surface properties due to the effect of polishing mixtures, heating or melting of the samples of metals and alloys by mechanical friction, laser radiation are not taken into account.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adherend surface is mechanically or chemically treated to obtain the desired porosity and rough adherend surface morphology. Chemical treatments involve polishing, etching, anodizing and other special treatments such as plasma and laser techniques [9][10][11][12][13][14][15][16][17][18]. Studies have shown that a two-stage polarization process can increase surface porosity and roughness [19].…”
Section: Introductionmentioning
confidence: 99%